2016
DOI: 10.1530/joe-16-0199
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of beta3 adrenergic receptor increases susceptibility to DIO in mouse

Abstract: The brown adipose tissue (BAT) mediates adaptive changes in metabolic rate by responding to the sympathetic nervous system through β-adrenergic receptors (AR). Here, we wished to define the role played by the ARβ3 isoform in this process. This study focused on the ARβ3 knockout mice (ARβ3KO), including responsiveness to cold exposure, diet-induced obesity, intolerance to glucose, dyslipidaemia and lipolysis in white adipose tissue (WAT). ARβ3KO mice defend core temperature during cold exposure (4°C for 5 h), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Recent research shows intact BAT thermogenesis despite the lack of β3AR in β3ARKO mice. β3-AR is essential for lipolysis but not to brown adipose thermogenesis (Preite et al, 2016). In the present study, EA was found to increase the expression of the UCP1 and β3 adrenergic receptor in HFD rats.…”
Section: Discussionsupporting
confidence: 48%
“…Recent research shows intact BAT thermogenesis despite the lack of β3AR in β3ARKO mice. β3-AR is essential for lipolysis but not to brown adipose thermogenesis (Preite et al, 2016). In the present study, EA was found to increase the expression of the UCP1 and β3 adrenergic receptor in HFD rats.…”
Section: Discussionsupporting
confidence: 48%
“…The ANS also influences local inflammatory responses in visceral and somatic tissues, via adrenergic and cholinergic receptor-mediated regulation of immune cells, connective tissue, and cardiovascular functioning. The ANS plays a major role in fat cell metabolism, vascular remodeling, and fibrosis associated with chronic inflammation [ 10 , 70 , 71 , 72 , 73 , 74 , 75 ]. The prevalence of chronic inflammation increases in frequency with advancing age, and may significantly contribute to premature aging, for which the term inflammaging has been coined [ 76 , 77 ].…”
Section: Autonomic Innervation Of the Spleen And Systemic Inflammamentioning
confidence: 99%
“…There is reduced β3-AR mRNA expression in adipose tissue in non-pregnant offspring derived from diet-induced obese dams [28]. It was learned from β3-AR knockout mice that reductions in this signaling pathway increases the susceptibility to HFD-induced obesity [29]. It has also been demonstrated in humans that activation of β-AR signaling significantly reduces body weight and fat [30].…”
Section: Plos Onementioning
confidence: 99%